100 days in photographs pivotal events that changed the world - Yapp, Nick (National Geographic and Getty Images, 2007)
This book is a visual journey through our age. To create it, Getty Images and National Geographic identified 100 days that represent defining moments of the past 150 years, and crystallized them with photographs that evoke joy and anger, triumph and despair--including scores of rare and unpublished photographs uncovered during its creation. From the Getty Images archive, images depict major world events. National Geographic's contributions illustrate scientific, cultural, and geographical topics. Politics, war, crime, technology, achievement, fads, and fashion all figure into the life and legacy of these 100 days. Supporting the visuals are firsthand journal excerpts, photographers' on-site notes, and insightful text by photography historian Nick Yapp.--From publisher description.
Includes bibliographical references and index
Keywords: Weltgeschichte 1851-2005; World history -- Pictorial works; History, Modern -- Pictorial works; Bildband